2018
DOI: 10.3389/fcvm.2018.00172
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins in Cardiovascular Calcification: Potential Targets and Challenges

Abstract: Previously considered a degenerative process, cardiovascular calcification is now established as an active process that is regulated in several ways by lipids, phospholipids, and lipoproteins. These compounds serve many of the same functions in vascular and valvular calcification as they do in skeletal bone calcification. Hyperlipidemia leads to accumulation of lipoproteins in the subendothelial space of cardiovascular tissues, which leads to formation of mildly oxidized phospholipids, which are known bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 135 publications
1
23
1
Order By: Relevance
“…Their data approved that atorvastatin can protect VSMC differentiation from TGF-β1-stimulated calcification through suppression of β-catenin pathway [ 35 ]. Their data are consistent with the recently results that atorvastatin could reduce arterial calcification and plasma calcium concentration [ 45 ] (Fig. 1 ).…”
Section: Autophagy Affects Vascular Calcification By Interfering With the Osteogenic Differentiation Of Vsmcssupporting
confidence: 93%
“…Their data approved that atorvastatin can protect VSMC differentiation from TGF-β1-stimulated calcification through suppression of β-catenin pathway [ 35 ]. Their data are consistent with the recently results that atorvastatin could reduce arterial calcification and plasma calcium concentration [ 45 ] (Fig. 1 ).…”
Section: Autophagy Affects Vascular Calcification By Interfering With the Osteogenic Differentiation Of Vsmcssupporting
confidence: 93%
“…Apart from being an established cardiovascular risk factor, Lp(a) recently emerged as a potential biomarker for CAC volume progression [ 46 ]. Moreover, earlier studies demonstrated positive correlation between Lp(a) and MGP levels hypothesizing that the high levels of MGP associated with Lp(a) are owing to a negative feedback loop [ 47 , 48 ]. In addition, Lp(a) also emerged as a viable therapeutic target since it has been shown that it may significantly contribute to residual cardiovascular risk in patients with CAD and optimal LDL-C levels [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 inhibitors attenuate local vascular inflammation and accelerate plaque delipidation when added to statins [ 37 ]. However, unlike statins, PCSK9 inhibitors have the benefit of lowering lipoprotein (a), a lipoprotein known to potentiate vascular calcification [ 38 , 39 ]. Macrocalcifications are best visualized on cardiac-gated CT imaging without contrast.…”
Section: Inflammation and The Pathobiology Of Atherosclerosismentioning
confidence: 99%